2016
DOI: 10.5812/jhealthscope.40416
|View full text |Cite
|
Sign up to set email alerts
|

Application of Different Isotherm Models for Humic Acid Adsorption on to Bentonite and Montmorillonite Nanoparticles

Abstract: Background: Adsorption isotherms describe the relationship between the equilibrium concentration of the adsorbed matter in the solution and the amount of adsorbed matter on the surface of the adsorbent. Objectives:The main objective of the present research was to investigate different adsorption isotherms for describing adsorption of humic acid by nanoclay. Methods:In this study, Langmuir, Freundlich, BET, Temkin and Dubinin Radushkevich isotherms, for describing the behavior of humic acid adsorption by benton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The constant K T (l mg −1 ) and Temkin constant b T values were found to decrease when the temperature increased, which could evaluate the exothermic nature of the adsorption system. Like the Freundlich isotherm model, the Halsey model is suitable for multilayer adsorption as well as the heterogeneous surfaces in which the adsorption heat is non-uniformly distributed [50]. In this study, the Halsey model fits well with the equilibrium data (R 2 , 0.9563-0.9917), confirming that MMIP MAA-βCD is a heterogeneous system characterized by the presence of different types of binding sites with different binding energies [51].…”
Section: Isotherm Adsorption Studysupporting
confidence: 64%
“…The constant K T (l mg −1 ) and Temkin constant b T values were found to decrease when the temperature increased, which could evaluate the exothermic nature of the adsorption system. Like the Freundlich isotherm model, the Halsey model is suitable for multilayer adsorption as well as the heterogeneous surfaces in which the adsorption heat is non-uniformly distributed [50]. In this study, the Halsey model fits well with the equilibrium data (R 2 , 0.9563-0.9917), confirming that MMIP MAA-βCD is a heterogeneous system characterized by the presence of different types of binding sites with different binding energies [51].…”
Section: Isotherm Adsorption Studysupporting
confidence: 64%
“…As depicted from Figure 4 , there is a VSM plot exhibited a value of 53 emu/g regarding the saturation magnetization of BFO/CFO@PEG. This results also confirmed from the relative literature, concerning the pure magnetite colloidal nanocrystals (36.941 emu/g) [ 62 ]. Noticeably, by using an external magnetic field, it can be observed that the nano-adsorbent can be separated relatively easily from the supernatant after adsorption process because of its magnetized properties.…”
Section: Resultssupporting
confidence: 90%
“…The SEM images revealed that the platelets of bentonite in f -MB have not formed normal bentonite sheets, but have been restructured in a more compact formation with great porosity (Figure 2). In fact, humic acid binding in bentonite and montmorillonite is known to create dense nanoclay structures [45].…”
Section: Resultsmentioning
confidence: 99%